Limits on the 21 cm Power Spectrum at z = 6.5–7.0 from Murchison Widefield Array Observations - C. D. Nunhokee; D. Null; C. M Trott; N. Barry; Y. Qin; R. B. Wayth; J. L. B. Line; C. H. Jordan; B. Pindor; J. H. Cook; J. Bowman; A. Chokshi; et al. (The Astrophysical Journal)
This paper presents the spherically averaged 21 cm power spectrum derived from Epoch of Reionization (EoR) observations conducted with the Murchison Widefield Array (MWA). The analysis uses EoR0-field data, centered at (R.A. = 0 h , decl. = −27 ^∘ ), collected between 2013 and 2023. Building on the improved methodology described in C. M. Trott et al. (2024), we incorporate additional data quality control techniques introduced in C. D. Nunhokee (2020). We report the lowest-power-level limits on the EoR power spectrum at redshifts z = 6.5, z = 6.8, and z = 7.0. These power levels, measured in the east–west polarization, are (30.2) ^2 mK ^2 at k  = 0.18 h Mpc ^−1 , (31.2) ^2 mK ^2 at k  = 0.18 h Mpc ^−1 , and (39.1) ^2 mK ^2 at k  = 0.21 h Mpc ^−1 , respectively. The total integration time amounts to 268 hr. These results represent the deepest upper limits achieved by the MWA to date and provide the first evidence of the heated intergalactic medium at redshifts z = 6.5 to 7.0.